PENGARUH EMPLOYER BRAND ATTRACTIVENESS TERHADAP INTENTION TO APPLY DI PT EIGERINDO MPI YANG DIMEDIASI OLEH ORGANIZATIONAL REPUTATION PADA GENERASI Z - Onaris, Angellica Putri; Dian Lestari (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
As time goes by and the level of competition becomes tighter, organizational resources must increasingly develop, including employees as human resources in the organization. To meet the need for quality human resources, companies must try to attract the interest of many job applicants. Currently, several large companies in Indonesia have implemented employer brand attractiveness, one of which is PT. EIGERINDO MPI, however, since the implementation of employer brand attractiveness at PT EIGERINDO MPI, no research has been conducted regarding its impact on intention to apply, so the aim of this research is to determine the effect of employer brand attractiveness on intention to apply which is mediated by good organizational reputation at PT. EIGERINDO MPI partially or simultaneously. The method in this research uses quantitative methods with data analysis, namely multiple regression analysis and assisted using SPSS 26.0. The data collection technique in this research was through distributing questionnaires to a total of 50 Generation Z applicants at PT EIGERINDO MPI. The results of this research show that (1) employer brand attractiveness has a positive effect on employee intention to apply, (2) organizational reputation can mediate the influence of employer brand attractiveness on employee intention to apply, and (3) employer brand attractiveness has an effect on intention to apply in PT. EIGERINDO MPI mediated by organizational reputation in Generation Z.